Tribunos de la plebe, provocatio ad populum y multitudo. Una reflexión sobre los límites del poder político en Roma - Ribas Alba , José María (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2009)
The protection of libertas in Roman Constitutional Law lies on a complex institutional framework. Amongst the protective mechanisms we highlight the provocatio ad populum and the tribunitia potestas. However, the study of these elements has to take account of the fact that the practical application of these is conditional on purely political pressure factors. The conformist popular action of public opinion plays a conclusive role. Populus, plebs and multitudo as political players set the limits to the application of the constitutional rule. This political influence does not mean denying the existence of legal rules, but rather it provides the legitimacy of its sense.
Keywords: Political freedom in Rome; Plebeian tribune; Auxilium; Provocatio ad populum; Multitudo; Public opinion